Hubungan Pendidikan, Usia dan Status Pekerjaan dengan Pemakaian Alat Kontrasepsi dalam Rahim (AKDR) di Puskesmas Pedamaran Kecamatan Pedamaran Kabupaten Oki Tahun 2019 - Esti Agustina; Merisa Riski; Rini Gustina Sari (Universitas Batanghari Jambi, 2021)
Family planning programs are now urgently needed to prevent unwanted pregnancies and to improve the health and well-being of mothers and children. This study is to determine the relationship between education, age and work status simultaneously with the use of intrauterine devices (IUD) at Pedamaran Public Health Center, Pedamaran District, OKI Regency in 2019. This research is a quantitative research type descriptive research using a cross sectional approach with a sample size of 98 respondents. with systematic random sampling technique. The data was collected by looking at and recording data on family planning acceptors in the medical records where there were variables of education, age and work status using a checklist designed by the researcher. This research was conducted from March to August 2020. Based on the analysis, it was found that there was a significant relationship between education (ρ value 0.027), age (ρ value 0.005), work status (ρ value 0.026) and the use of intrauterine contraceptives (IUD) in Pedamaran Public Health Center, Pedamaran District, OKI Regency in 2020. The conclusion in this study can be seen that there is a relationship between education, age and employment status with the use of intrauterine contraceptives (IUD) at Pedamaran Puskesmas Pedamaran District, OKI Regency in 2019.